Föderalizmus és szubszidiaritás az Európai Unióban - Dömök, Csilla (Közép-Európai Közlemények, 2023)
Nowadays, federalism and subsidiarity have become the watchwords of the political discourse around European integration and its further development. Both are used to oppose the dreaded centralism of the European Union and to prevent the undermining of the competences of the member states. On the other hand, they reject federalism and sovereignty because it could open the door to a further strengthening of the European Union at the expense of the sovereignty of the Member States. Despite different conceptual interpretations and the resulting frontal positions, what have in common is that they differ from the path on which European integration is moving forward, in which competences are transferred from the Member States to the European Community, even if European unity is generally recognised. Behind the conceptual façade lies first of all the traditional explanation of the organisational division and division of competences between the Community and the Member States.